Transnational organized crime - Madsen, Frank G. (Routledge global institutions, 2009)
Taxonomy -- History and development of concept of organized crime -- The transnational crimes -- Transnational crime and terrorism -- The economics of transnational organized crime -- Initiatives against transnational crime -- Critical issues and future trends